Community Participation in Environmental Protection and Management in Ecotourism Development in Sikasur Tourism Village, Belik District, Pemalang Regency - Widya Anugrah Saputri (UMPurwokerto Law Review, 2022)
AbstractAs an agricultural country, Indonesia has a wealth of biological natural resources, which, in addition to acting as a source of food and foreign exchange, also has an attraction in the nature tourism sector (ecotourism). One of the natural attractions in Pemalang Regency is the Sikasur Tourism Village. To realize sustainable ecotourism development, it is necessary to identify the extent of community participation in environmental protection and management in Sikasur Village. The research method used in this study is a normative juridical method carried out through a literature study that examines mainly secondary data. This research is descriptive by describing the applicable laws and regulations associated with legal theory related to the problem. Based on the research results, it is known that the participation of the Sikasur Tourism Village community in environmental protection for ecotourism development is formed by the existence of a tourism awareness group (Kelompok Sadar Wisata, Pokdarwis) which is managed directly by the Village Owned Enterprise (Badan Usaha Milik Desa, BUMDes). Many efforts have been made in environmental law enforcement, but in practice, there are still obstacles and obstacles encountered in environmental protection efforts in the development of ecotourism in Sikasur Tourism Village, Pemalang Regency.Keywords: Environmental Protection, Ecotourism, Tourism Village AbstrakIndonesia sebagai negara agraris memiliki kekayaan sumber daya alam hayati yang disamping berperan sebagai sumber pangan dan devisa negara, juga mempunyai daya tarik dalam sektor pariwisata alam (ecotourism). Salah satu objek wisata alam yang ada di Kabupaten Pemalang terdapat di Desa Wisata Sikasur. Sebagai upaya untuk mewujudkan pengembangan ekowisata yang berkelanjutan perlu dilakukan suatu identifikasi sejauh mana peran serta masyarakat terhadap perlindungan dan pengelolaan lingkungan di Desa Sikasur. Metode penelitian yang digunakan dalam penelitian ini adalah metode yuridis normatif yang dilakukan melalui studi pustaka yang menelaah terutama data sekunder. Penelitian ini bersifat deskriptif dengan menggambarkan peraturan perundang-undangan yang berlaku dikaitkan dengan teori hukum yang berkaitan dengan permasalahan. Berdasarkan hasil penelitian diketahui peran serta masyarakat Desa Wisata Sikasur dalam perlindungan lingkungan terhadap pengembangan ekowisata dibentuk dengan adanya kelompok sadar wisata (Pokdarwis) yang dikelola langsung oleh Badan Usaha Milik Desa (Bumdes). Banyak upaya telah dilakukan dalam rangka penegakan hukum lingkungan, namun dalam pelaksanaannya masih terdapat kendala dan hambatan yang ditemui pada upaya perlindungan lingkungan dalam pengembangan ekowisata di Desa Wisata Sikasur Kabupaten Pemalang. Kata Kunci : Perlindungan Lingkungan, Ekowisata, Desa Wisata